High site fidelity in Northern Wheatears Oenanthe oenanthe wintering in Africa revealed through colour marking. Issue 2 (2nd April 2016) - Blackburn, Emma; Cresswell, Will
ABSTRACT: Wintering Northern Wheatears Oenanthe oenanthe in the Sahel region of Northern Nigeria held small (approximately 70 m diameter) distinct territories during the study period, and territory size did not differ between adult and first winter birds. Evidence suggests that Wheatears may maintain small territories for a significant duration of the winter, similar to many other migrants.